Pro Hibernate 3 - Minter, Dave. (Apress : Imprint: Apress, 2005)
Pro Hibernate 3 is the first book to offer complete coverage of the open source lightweight Hibernate 3 and its features. Authors Dave Minter and Jeff Linwood discuss the persistence layer and share design tips and best practices. And the duo goes beyond just explaining how to use parts of Hibernate; they probe well beneath the surface, and teach you how to step back and solve problems thoroughly. If you have experience using Java with databases, but lack experience with Hibernate, then this book is ideal for you. Similarly, if you have some familiarity with Hibernate 2 and now want to learn the nuances of version 3, then this book is a wise addition to your library.